Mechanical and psychophysical performance evaluation of a haptic actuator based on magnetorheological fluids. (August 2016) - Ryu, Semin; Koo, Jeong-Hoi; Yang, Tae-Heon; Pyo, Dongbum; Kyung, Ki-Uk; Kwon, Dong-Soo
This study presents a miniature haptic actuator (10 mm (L) × 10 mm (W) × 6.5 mm (H)) based on magnetorheological fluids, which is designed to provide realistic touch sensations to users. Its primary goals are to evaluate mechanical or actuation performances of the prototype magnetorheological actuator and to assess its effectiveness in conveying haptic sensations to users by conducting the psychophysical experiments. The mechanical performance study evaluated the prototype's output forces from haptic perspectives using a dynamic test frame. The psychophysical experiments studied human subjects' perceptions on haptic sensations produced by the prototype. The mechanical test results show that the magnetorheological actuator is capable of generating a wide range of frequency-dependent output forces (from 1.5 N to nearly 9 N). The psychophysical experiments show that the actuator offers various kinesthetic and vibrotactile sensations to human operators. Overall, the results suggest a feasibility of using the magnetorheological haptic actuator in real-world applications, such as a haptic keypad and functional buttons in small consumer electronics and hand-held devices.